GESTALT GAME TO IMPROVE STUDENTS’ ADAPTABILITY IN PONDOK PESANTREN - Rahman, Imas Kania; Furqon, Furqon (UPI Press, 2011)
This study aims at finding the effectiveness of guidance and counselling through GestaltGame technique in improving students’ adaptability in two Islamic boarding schools. Thestudy was conducted by using a pretest-posttest nonequivalent group design involving fourgroups of students from two different Islamic boarding schools. The study considered theinflunce of gender and boarding school environment towards the effectiveness of GestaltGame. It was conducted by controlling heterogenity in students’ adaptability before thetreatment as well as students’ religiosity. The study shows that Gestalt Game is effectivein improving adaptability of the students in the two Islamic boarding schools involvedin the study. Moreover, the study reveals that Gestalt Game does not affect gender andIslamic boarding schools’ environment.Keywords: Gestalt Game; students’ adaptability; students’ religiosity